Description of Bucephalus anguillae n. sp. (Trematoda: Bucephalidae), a Parasite of the Eel Anguilla anguilla (Anguillidae) from a Brackish Water Lagoon of the Adriatic Sea - Spakulova, M.; Macko, J. K.; Berrilli, F.; Dezfuli, B. S. (The Journal of Parasitology, 2002)
The digenetic trematode Bucephalus anguillae n. sp. is described from the intestine of eel, Anguilla anguilla L., originating from a brackish water fish farm on the Italian coast of the Adriatic Sea. The new taxon is 1 of 12 Bucephalus species characterized by an anterior rhynchus surrounded by 7 tentacular appendages, each when fully protruded with 2 prongs. Scanning electron microscopy reveals, for the first time in a Bucephalus species, the crescent-shaped, unspined field located between the rhynchus and the dorsal tentacles. A comparison of B. anguillae n. sp. with 11 congeneric species revealed its remarkable similarity with B. polymorphus Baer, 1827; however, the new species has a larger cirrus sac, larger pharynx, vitelline gland fields not extending the level of pharynx, ovary located in the pharyngeal area rather than fairly posterior to pharynx, smaller testes, relatively wider rhynchus, and tegumental armature comprising slightly larger spines. Multivariate discriminant analyses confirmed a differentiation of B. anguillae from populations of B. polymorphus; the combination of 4 variables, namely cirrus sac length, pharynx width, cirrus sac width, and rhynchus width yielded a total separation of compared species.